Granite Exploration by using Electrical Resistivity Imaging (ERI): A Case Study in Johor - Ishak, Mohd Fakhrurrazi; Zaini, M. S. I; Zolkepli, M.F; Wahap, M. S; Sidek, J. I. Jaafar; Yasin, A. Mohd; Zolkepli, M. N.; Mohmad Sidik, M. H.; Mohd Arof, K. Z.; Abu Talib, Z. (International Journal of Integrated Engineering, 2020)
Electrical Resistivity Imaging (ERI) is a tool used in near surface geophysical surveys by flowing an electric current through electrodes that were injected into the ground. The usage of electrical resistivity imaging (ERI) method dominated by geophysicist has increased tremendously in geotechnical engineering application owing to the efficiency and effectiveness of the method in term of time, cost and also data coverage. The survey performed with respect to the particular reference to ERI in determining the granite rock underneath the ground. There were seven (7) lines of ERI performed at the study area by using ABEM Terrameter LS 2 set of equipment based on Schlumberger protocol. Six (6) boreholes were also drilled to obtain engineering properties of rock at the study area. In order to develop the relationship between resistivity and engineering properties, a comparison between borehole field test result and the resistivity value were made. Results from the ERT indicated the presence of zones with high resistivity values identified as overburden soil, fractured granite and solid granite. The findings of this study also showed that the electrical resistivity imaging coupled with borehole drillings were applicable tools for the determination of the granite rock underneath the ground via subsurface profiles and such as depth of overburden soil and engineering properties of soil.